Political and gender narratives: An immersion in contemporary Italy through the social lens on women leaders - Battista, Daniele (Comunicación y Género [Communication and Gender], 2023)
This article presents a comparative analysis between two prominent figures in contemporary Italian politics, Giorgia Meloni and Elly Schlein, with a particular focus on the gender dynamics that permeate their political context and influence their public trajectory. Through an in-depth exploration of their political narratives, the analysis centers on the use of gender as a central element in both leaders’ strategies. The initial phase of the analysis involved a quantitative assessment conducted through social data analysis to understand the extent of online presence and influence of the two political figures under examination. Only subsequently are the discourses and public communications related to women, family, and gender issues highlighted and analyzed. This research aims to provide a unique perspective on how political and gender positions influence politics and contribute to an understanding of contemporary political dynamics in Italy